Problem-Based Learning Approach in Solving Mathematical Word Problems Among Sixth Grade Students - Novianti, Wiwin; Nurfitriana, Nurfitriana; Saepuddin, Diana; Rachayu, Tatik Susanty; Darwati, Darwati; Sajiman, Supardi Uki; Suhendri, Huri (ATTA`DIB, 2026)
Mathematics learning, especially in the topic of word problems, remains a challenge for elementary school students because it requires the ability to understand context, reasoning, and problem solving. This study aims to examine the effectiveness of the implementation of the Problem-Based Learning (PBL) model in improving the ability of sixth-grade students of SDN Pengadegan 07 Pancoran, South Jakarta, in solving mathematical word problems on the topic of comparison, as well as identifying the process and obstacles in its implementation. This study used a mixed methods approach with a sequential explanatory design. The research sample consisted of 30 sixth-grade students. The initial hypothesis of this study was that the implementation of the PBL model had an effect on students' ability to solve mathematical word problems. Quantitative data were obtained through a test of the ability to solve word problems, while qualitative data were collected through observations and interviews with teachers and students. The pretest results showed a moderate average initial ability score of 50. The results of the study showed that the implementation of PBL was able to improve students' abilities, indicated by a high average test score of 84 and increased student activity and participation in learning. Furthermore, the results of the paired sample t-test revealed a statistically significant difference between the pretest and posttest scores (p < 0.05), which confirmed that the increase was significant. Qualitative data also showed that PBL helped students understand problems more deeply through discussions and contextual problem solving, despite obstacles such as limited learning time and low reading comprehension skills of some students.